How to measure the immunosuppressive activity of MDSC: assays, problems and potential solutions - Bruger, Annika M.; Dorhoi, Anca; Esendagli, Gunes; Barczyk-Kahlert, Katarzyna; van der Bruggen, Pierre; Lipoldova, Marie; Perecko, Tomas; Santibanez, Juan; Saraiva, Margarida; Van Ginderachter, Jo A.; Brandau, Sven (Cancer Immunology, Immunotherapy, 2019)
Myeloid-derived suppressor cells (MDSC) are a heterogeneous group of mononuclear and polymorphonuclear myeloid cells, which are present at very low numbers in healthy subjects, but can expand substantially under disease conditions. Depending on disease type and stage, MDSC comprise varying amounts of immature and mature differentiation stages of myeloid cells. Validated unique phenotypic markers for MDSC are still lacking. Therefore, the functional analysis of these cells is of central importance for their identification and characterization. Various disease-promoting and immunosuppressive functions of MDSC are reported in the literature. Among those, the capacity to modulate the activity of T cells is by far the most often used and best-established read-out system. In this review, we critically evaluate the assays available for the functional analysis of human and murine MDSC under in vitro and in vivo conditions. We also discuss critical issues and controls associated with those assays. We aim at providing suggestions and recommendations useful for the contemporary biological characterization of MDSC.